(untitled) (UNED Research Journal, 2018)
In the search to develop the production of vegetable oils for non-food purposes biodiesel stands out for its great versatility as technical material and a cleaner energy technology. Physic nut (Jatropha curcas), castor-oil (Ricinus communis), oil palm (Elaeis guineensis), wine palm (Attalea butyracea) and macaw palm (Acrocomia aculeata) were chosen for study in our laboratory, because they are oleaginous plants with convenient oil yields to produce biodiesel. No significant effect from the nature of fatty-acid chains in biodiesel is observed on thermodynamic properties such as heat of combustion, cubic-expansion thermal coefficient, isothermal compressibility, enthalpy of vaporisation and Hildebrand solubility parameter. Activation energies for viscous flow of biodiesels correlates with the same property of their vegetable oil feedstocks.